PLGA-particle vaccine carrying TLR3/RIG-I ligand Riboxxim synergizes with immune checkpoint blockade for effective anti-cancer immunotherapy - Julia Koerner (Nature Portfolio, 2021)
PLGA based cancer immunotherapy incorporating antigen and TLR ligands has resulted in enhancement of the anti-tumour response. Here, the authors explore the use of a defined double stranded RNA adjuvant, Riboxxim, and test its incorporation with PLGA immunotherapy in the context of in vivo tumour models and show enhanced induction of the anti-tumour response.